Neurodevelopmental Outcomes in Extracorporeal Membrane Oxygenation Patients: A Pilot Study. Issue 4 (April 2020) - Dhar, Archana V.; Scott, Stacey; Anton-Martin, Pilar; Tweed, Jefferson; Morris, Mary Ann; Modem, Vinai; Raman, Lakshmi; Golla, Sailaja
Abstract : In this pilot study, we evaluated the long-term neurodevelopmental outcomes in neonatal and pediatric patients supported by extracorporeal membrane oxygenation (ECMO) and aimed to identify the role of post-ECMO magnetic resonance imaging (MRI) in predicting neurodevelopmental outcomes. Twenty-nine patients were evaluated using the Ages and Stages Questionnaire, Third Edition (ASQ-3) screening tool. Thirteen were evaluated during their visit at the neurodevelopmental clinic and 16 were interviewed via phone. We also reviewed the post-ECMO MRI brain of these patients and scored the severity of their injury based on the neuroimaging findings. In our cohort of 29 patients, 10 patients (34%) had developmental delay. Of those with developmental delay, 80% were newborns. Sixty-seven percent of patients with developmental delay had moderate to severe MRI abnormalities as compared with only 18% with no developmental deficits ( p = 0.03). The younger the age at the time of placement on ECMO, the higher the chances of impaired neurodevelopmental outcome. Long-term follow-up of patients who have survived ECMO, with standardized neuropsychologic testing and post-ECMO imaging, should become the standard of care to improve long-term outcomes. Significant abnormalities on brain MRIs done before discharge correlated with developmental delay on follow-up.